Process Evaluation of MAPS: A Highly Tailored Digital Intervention to Support Medication Adherence in Primary Care Setting - Kassavou, Aikaterini; Court, Charlotte A.; Mirzaei, Venus; Brimicombe, James; Edwards, Simon; Sutton, Stephen (Frontiers in Public Health, 2021)
Background. Medication adherence can prevent health risks, but many patients do not adhere to their prescribed treatment. Our recent trial found that a digital intervention was effective at improving medication adherence in non-adherent patients with Hypertension or Type 2 Diabetes; but we do not know how it brought about behavioural changes. This research is a post-trial process evaluation of the mechanism by which the intervention achieved its intended effects. Methods. A mixed methods design with quantitative and qualitative evidence synthesis was employed. Data was generated by two studies. Study 1 used questionnaires to measure the underlying mechanisms of and the medication adherence behaviour, and digital logfiles to objectively capture intervention effects on the process of behaviour change. Multilevel regression analysis on 57 complete intervention group cases tested the effects of the intervention at modifying the mechanism of behaviour change and in turn at improving medication adherence. Study 2 used in depth interviews with a subsample of 20 intervention patients and 8 practice nurses. Thematic analysis provided evidence about overarching intervention functions and recommendations to improve intervention reach and impact in primary care. Results. Study 1 found that intervention effectiveness was significantly associated with positive changes in the underlying mechanisms of behaviour change (R2=0.26, SE=0.98, P=0.00); and this effect was heightened twofold when the tailored intervention content and reporting on medication taking (R2=0.59, SE=0.74, P=0.00) was interested into the regression model. Study 2 suggested that the intervention supported motivation and ability to adherence, although clinically meaningful effects would require very brief advice and signposting to ongoing behavioural support during clinical consultations. Conclusion. This post trial process evaluation used objective methods to capture the intervention effect on the mechanisms of behaviour change to explain intervention effectiveness, and subjective accounts to explore the circumstances under which these effects were achieved.